Cloud Based Decision Support System for Waste-Water Management using Supervised Decision Tree Algorithm - Bhavsar, A K; Shah, J S (International Journal of Computer Sciences and Engineering, 2025)
As reuse is gaining popularity, there is challenge for the wastewater reusability also. Now a day’s lots of research work are in boon for such system. In context with this there is need to develop systems which help to decision maker where to use wastewater. Population grows with rising standard of living; more wastewater is generated and disposed to sensitive environments with negative impact on humans and ecosystems. The aim of this research is to develop a DSS by using Machine Learning technique specifically supervised Decision Tree Algorithm, which is intended for applying intelligent decisions supporting reuse of wastewater management. This developed system provides best decision for the reuse of wastewater after the treatment. Further this system is deployed on cloud, as Cloud computing provides a good manageability and fast computational service. Currently its very challenging for exiting system stakeholders specifically ( Municipal Corporation or user) to use this type of cloud based DSS for waste water. To upgrade this management scenario, this research project proposes CBDSSWWM.